CERTAIN PROPOSALS OF THE CONSUL IN PRIŠTINA FOR IMPROVING THE SITUATION OF THE SERBIAN POPULATION (1889–1905) (Heritage, 2022)
Thanks to the diplomatic work of Serbia and the engagement of its politicians, a consular convention was signed, on the basis of which consulates in the Ottoman Empire were opened. Among the open consulates, the consulate in Priština was of special importance for the Serbian people. Its consuls dealt almost exclusively with the difficult situation of the Serbian people, as evidenced by numerous reports sent to the Government in Belgrade. There were no other consulates in Priština and there was a great need for its work and protection of the large Serbian population north of the Šara Mountain. The position of Serbs in the area of ​​the Priština consulate was hampered not only by the work of Turkish officials, but also by the anarchy and daily tyranny of Albanians, towards which the authorities were lenient.            From its founding in 1889 until the liberation in 1912, ten consuls served in the consulate in Priština. It was not uncommon for clerks or dragomans to perform duties in the absence of consuls. Not only did they perform the service, but they also left very valuable written notes of that time, which occupy an important place in domestic historiography.The consuls of the Kingdom of Serbia in Priština witnessed various atrocities against the Serbian population by Albanians. The Turkish authorities acted negligently and did not show the will to take appropriate measures against the rioters. That is why, from the very opening of the consulate, various proposals could be heard, which were sent to the Government in Belgrade. Some of them referred to bringing the consuls closer to the Albanians, establishing contacts and cooperation with the leaders of Albanians, abolishing the consulate and finally arming the Serbian population. The consuls often insisted that the domestic and foreign press be engaged, because they thought that its actions would influence Porta and the sultan to prevent oppression of the Serbian population which, under the pressure, left their property and emigrated outside the Ottoman Empire.
Keywords: Consulate in Priština, consuls, propasals, Serbs, Albanians, oppressings